Production of Bio-Ethanol from Various Lignocellulosics Using High Yielding Isolate of Saccharomyces Cerevisiae Apn07: Mathematical Approach - G. Narendra Kumar (Journal of Global Pharma Technology, 2018)
Bio ethanol is increasingly being used as fuel additive in automobiles and the maximization of its production from alternative renewable substrates like lignocellulosic materials are gaining significance. The present study attempts to optimize the media using 0.5% acid hydrolysates from rice husk, rice straw, and sugarcane bagasse and groundnut shell with sugarcane molasses for the production of bio ethanol using RSM analysis with CCD design. The strain of Saccharomyces cerevisiae APN 07 isolated from coconut toddy that yielded 9.6% ethanol when 1.5 ml of all five substrates were mixed in the combination of 15 ml each. Mathematical analysis of the results determined the correctness of the prediction. The coefficient of determination (R2) was 0.997034 signify that the response model could revealed 99.19 % of total difference. The value of (R2pred = 0.994989) indicates high accord between the experimental and predicted value. The high value of adjusted determination coefficient (R2adj¬= 0.993) indicated the significance of model. FTIR confirms the presence of alcohol (OH group). Batch kinetic studies agreed with the model for ethanol production.Keywords: Saccharomyces cerevisiae APN 07, RSM-CCD, Alcohol production.